THE PUBLIC PASSENGER TRANSPORT AS A FACTOR OF SUSTAINABLE REGIONAL DEVELOPMENT - Zaloga, Elzbieta; Milewski, Dariusz (Doprava a spoje, 2012)
Passenger regional public transport plays very important role in a region and could be essential factor of its sustainable development of a country and a region. It is quite difficult however to assess the measurable impact of this form of transport on regional development, especially in economical aspects. Problem is essential, because passenger transport is very often unprofitable and needs financial support from regional authorities.